As folias de reis em Quirinópolis (GO): ressignificações da tradição e das relações sociais nos espaços urbano e rural na contemporaneidade. - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This work is an analysis of the Epiphany tradition, focusing on groups of revelers from the municipality of Quirinópolis in the state of Goiás. The research aimed to trace the origins, the adaptations, the resignifications of this religious and cultural manifestation and its role in defining the identities of revelers and devotees. The definition of the period of analysis included the years from 1918 to 2023, allowing an investigation about the changes in the cultural practices and representations in the municipality, due to the social and economic transformations in urban and rural environments that influenced the celebration of the Three Kings day. This is a study that values the everyday historical protagonist, therefore, the adoption of the technique of semi-structured interviews, use of iconography, audiovisual sources, bibliographic sources related to the subject, together with field research and participant observation were crucial for the execution of the analysis. Considering the relevance and cultural strength of popular festivities, especially the Three Kings day, several theoretical discussions about the festive phenomenon were investigated, with the aim of understanding its meaning and position, recognizing it as a facilitator between individual and community desires. The Three Kings day festival represents a place of memory built by the interventions and manifestations of the social members (the revelers and devotees). The investigation of the data indicated that even though the Three Kings day festivities have their origins in the colonial times, they continue to present, in the contemporary times, their specificities, with some changes and integrations, in an effort to preserve them for future generations.
The Epiphany tradition in Quirinópolis (GO): The resignifications of the tradition and the social relationships in the urban and rural areas in the contemporary times.
Keywords: Folia de Reis; Manifestação Religiosa; Tradição Popular; Patrimônio Cultural; Festas Religiosas; Religious Manifestation; Kings party; CIENCIAS HUMANAS::TEOLOGIA